Holy Cow! Astronomers agog at mysterious new supernova. (8th November 2018) - Castelvecchi, Davide
An event known as 'Cow' that has rocked astronomy since June likely offers a close look at the birth of a neutron star or black hole. An unusual event known as 'Cow' and first spotted in June has offered a close look at the formation of a neutron star or black hole.